Assessment of environmental capabilities and capabilities of Tarom city for olive production and cultivation - Vahid Riahi; saeid nasire zare (تحقیقات کاربردی علوم جغرافیایی)
Land surveying to increase crop production and productivity is nowadays considered as one of the alternative approaches in agricultural development and the need to address this issue especially in rural areas where their income is highly dependent on agriculture is of great importance. Is high. Agricultural development is one of the priorities of agricultural planning and requires such development to identify the effective factors that govern it. The purpose of this study was to evaluate and evaluate the environmental capabilities of olive cultivation in Tarom city and to analyze the location of its producing rural areas. Hence, from altitude, slope and slope status as terrestrial parameters and three climate parameters as relative rainfall, temperature and relative humidity data from 11 meteorological, synoptic and rain gauge stations with appropriate statistical period (1375-1395) and A common time base was used for climatic zoning. The results showed that Tarom city is in good condition for olive cultivation, 21.2% of the total area of the study area is suitable for olive cultivation, most of which is located in the middle districts of the city. Located in olive-growing lands, these areas produce 74.8 percent of the olive in Tarom, due to its olive-growing potential.